Pathophysiological mechanisms of neuropathic pain - Vollert, Jan; Magerl, Walter; Henrich, Florian; Klein, Thomas; Schuh-Hofer, Sigrid; Treede, Rolf-Detlef (Pain, 2018)
Abstract: As an indirect approach to relate previously identified sensory phenotypes of patients suffering from peripheral neuropathic pain to underlying mechanisms, we used a published sorting algorithm to estimate the prevalence of denervation, peripheral and central sensitization in 657 healthy subjects undergoing experimental models of nerve block (NB) (compression block and topical lidocaine), primary hyperalgesia (PH) (sunburn and topical capsaicin), or secondary hyperalgesia (intradermal capsaicin and electrical highfrequency stimulation), and in 902 patients suffering from neuropathic pain. Some of the data have been previously published. Randomized split-half analysis verified a good concordance with a priori mechanistic sensory profile assignment in the training (79%, Cohen k 5 0.54, n 5 265) and the test set (81%, Cohen k 5 0.56, n 5 279). Nerve blocks were characterized by pronounced thermal and mechanical sensory loss, but also mild pinprick hyperalgesia and paradoxical heat sensations. Primary hyperalgesia was characterized by pronounced gain for heat, pressure and pinprick pain, and mild thermal sensory loss. Secondary hyperalgesia was characterized by pronounced pinprick hyperalgesia and mild thermal sensory loss. Topical lidocaine plus topical capsaicin induced a combined phenotype of NB plus PH. Topical menthol was the only model with significant cold hyperalgesia. Sorting of the 902 patients into these mechanistic phenotypes led to a similar distribution as the original heuristic clustering (65% identity, Cohen k50.44), but the denervation phenotype was more frequent than in heuristic clustering. These data suggest that sorting according to human surrogate models may be useful for mechanism-based stratification of neuropathic pain patients for future clinical trials, as encouraged by the European Medicines Agency
Gesehen am 28.03.2019